Mamma mia! [videorecording (DVD)] : the movie - Streep, Meryl; Brosnan, Pierce; Firth, Colin, 1960-; Skarsgård, Stellan; Walters, Julie, 1950-; Cooper, Dominic, 1978-; Seyfried, Amanda; Baranski, Christine; Andersson, Benny (Universal Pictures Home Entertainment, 2018)
Sophie has just one wish to make her wedding perfect: to have her father walk her down the aisle. Now she just has to find out who he is.